Comparative Effectiveness of Acupoint-to-Acupoint Penetrating Needling Technique for Post-Stroke Spasticity: A Systematic Review and Meta-Analysis - Sul Gi Yoon; Mikyung Kim; Chang-ho Han (Journal of Korean Medicine, 2026)
Objectives: This study aimed to systematically evaluate the efficacy and safety of acupoint-to-acupoint penetrating needling (AAPN) technique compared with conventional acupuncture for patients with post-stroke spasticity.Methods: Randomized controlled trials (RCTs) were searched in PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure, ScienceON, Research Information Sharing Service, and Oriental Medicine Advanced Searching Integrated System. The primary outcomes were spasticity measured by the Modified Ashworth Scale (MAS) and total effective rate. Secondary outcomes included motor function (Fugl-Meyer Assessment, FMA), balance (Berg Balance Scale, BBS), activities of daily living (Barthel Index/modified Barthel Index, BI/MBI), and adverse events. A random-effects model was applied for the meta-analysis. Risk of bias was assessed using the Cochrane Risk of Bias 2 tool, and the certainty of evidence was evaluated using Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach.Results: Nineteen RCTs were included. Compared with conventional acupuncture, AAPN significantly improved MAS (MD −0.45, 95% CI −0.61 to −0.30), and the total effective rate was higher in the AAPN group (RR 1.21, 95% CI 1.12 to 1.30) (both p